1954
DOI: 10.1037/h0083619
|View full text |Cite
|
Sign up to set email alerts
|

A study of anxiety in a general hospital setting.

Abstract: "An attempt was made to measure anxiety in a realistic situation which offered the possibility of combining clinical and experimental approaches. Two types of anxiety were identified: situational and basic. Situational anxiety appeared to interfere temporarily with the subject's ability to solve a new problem or adapt to a novel experience. Basic anxiety, on the other hand, was found to reduce the subject's ability to relate to people and to assimilate experience. Such a finding is consistent with the belief t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1961
1961
2006
2006

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Time pressure can also increase rigidity of thinking on work‐related tasks such as selection decisions (Kruglansky & Freund, 1983). Wright (1954) asked people to respond to Rorschach inkblots tests; half were hospital patients awaiting an operation and half were “controls”. The former gave more stereotyped responses, and were less fluent and creative in completing similes (e.g.…”
Section: External Demandsmentioning
confidence: 99%
“…Time pressure can also increase rigidity of thinking on work‐related tasks such as selection decisions (Kruglansky & Freund, 1983). Wright (1954) asked people to respond to Rorschach inkblots tests; half were hospital patients awaiting an operation and half were “controls”. The former gave more stereotyped responses, and were less fluent and creative in completing similes (e.g.…”
Section: External Demandsmentioning
confidence: 99%
“…Time pressure can also increase rigidity of thinking on work-related tasks such as selection decisions (Kruglansky and Freund, 1983). Wright (1954) asked people to respond to Rorschach inkblots tests; half were hospital patients awaiting an operation and half were 'controls'. The former gave more stereotyped responses, and were less fluent and creative in completing similes (e.g.…”
Section: Ensure a High Level Of Extrinsic Demandsmentioning
confidence: 99%
“…Beam (1955) obtained measures before doctoral oral examinations and opening night performances in plays as well as at a less stressful period in the subject's life, and found marked impairment in learning a serial list of nonsense syllables, and an increase in palmar sweat and GSR conditioning rate under stress as compared to nonstress. Basowitz et al (1955) reported a tendency for digit span to be impaired for soldiers undergoing paratroop training as compared to a control group, and Wright (1954) likewise found impairment in digit span in patients confronted with the threat of surgery.…”
Section: Behavioral Measures: Experimental and Group Comparisonsmentioning
confidence: 99%